2018
DOI: 10.1111/bcpt.12955
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Approaches to Testing and Assessment: OECD Activities on the Development and Use of Adverse Outcome Pathways and Case Studies

Abstract: The Organisation for Economic Co-operation and Development (OECD) works with member countries and other stakeholders to improve and harmonize chemical assessment methods. In 2012, the OECD Adverse Outcome Pathways (AOPs) Development Programme started. The Programme has published six AOPs thus far and more than 60 AOPs are under various stages of development under the Programme. This article reviews recent OECD activities on the use of AOPs in developing Integrated Approaches to Testing and Assessments (IATAs).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(36 citation statements)
references
References 14 publications
0
36
0
Order By: Relevance
“…This assessment could be used for gap filling as well as the prediction of potential mechanisms to guide further investigations. A useful guideline on how AOPs can be integrated into risk assessment was published by Sakuratani and coworkers . Arzuaga and coworkers showed that the AOP framework can be used to identify and describe possible species‐specific effects .…”
Section: Adverse Outcome Pathwaysmentioning
confidence: 99%
“…This assessment could be used for gap filling as well as the prediction of potential mechanisms to guide further investigations. A useful guideline on how AOPs can be integrated into risk assessment was published by Sakuratani and coworkers . Arzuaga and coworkers showed that the AOP framework can be used to identify and describe possible species‐specific effects .…”
Section: Adverse Outcome Pathwaysmentioning
confidence: 99%
“…Integrated Approaches to Testing and Assessment (IATA) is a novel procedure outlining science‐based approaches for toxicological decision‐making based on the integration of multiple information sources from in vivo , in vitro and in silico . The IATA concept is a tool to promote risk assessment by non‐animal testing methods, and it is already used for some end‐points such as skin corrosion/irritation and skin sensitization, where validated in vitro tests are available and in conjunction with other relevant information .…”
Section: Iata For Integration Of Multiple Information Sourcesmentioning
confidence: 99%
“…The most important element in applying IATA is Adverse Outcome Pathway (AOP) concept where the toxicologically critical, molecular, biochemical and biological pathways or networks of pathways with key events are identified and in vitro assays developed to cover these pathways. OECD has published guidance documents on how to use AOPs in developing IATA . Six AOPs have been published so far .…”
Section: Iata For Integration Of Multiple Information Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, alternative test systems, such as human stem/progenitor cell and zebrafish models, have the potential to enable testing of large chemical libraries while reducing expense and minimizing rodent use [4,[20][21][22][23][24][25].In human stem/progenitor cell models, various endpoints have been used to assess DNT, including viability, apoptosis, proliferation, migration, differentiation, and neuronal network formation [24,26,27]. These endpoints facilitate the identification of adverse outcome pathways and the development of integrated approaches to test and assess chemical-induced DNT [22,28]. Differentiation of neural stem/progenitor cells into neurons, astrocytes, and oligodendrocytes has been analyzed by immunohistochemical staining with antibodies against cell-specific proteins such as NeuN/RNA-binding Fox3 (Rbfox3) for neurons, glial fibrillary acidic protein (GFAP) for astrocytes, and myelin basic protein (MBP) for oligodendrocytes [26,29].…”
mentioning
confidence: 99%